ASPECTS OF CHANNELS DECISION IN SMALL RETAIL: THE CHOISE BETWEEN THE TRADITIONAL WHOLESALE AND THE WHOLESALE AND RETAIL OUTLET - Hsien, Huang Wen; Cônsoli, Matheus Alberto; Giuliani, Antonio Carlos (Revista de Administração da UFSM, 2011)
This article talks about purchase decision from small and medium retailers from Piracicaba Region, São Paulo State. The bibliographic and field research showed the main influence factors and decision criteria of small retailers for purchase, related to the choice between the traditional wholesale and the wholesale and retail outlet, which is a type of store that allows the wholesaler sales to sell to small or medium-sized retailers and for end consumers who are looking for the best price. The topics treated are the distribution channels, types of agents, the role of each one and the retailers' decision of purchasing. The exploratory research was applied to small and medium-sized retailers from Piracicaba Region, Sao Paulo State Countryside. From the eight case studies it was possible to identify the aspects considered relevant for retailers in the purchase decision and partner choice. Retailers were expressed by five attributes considered the most relevant, they are: convenience, variety, price, reliability and quantity.